Discovery of the digger wasp genus Argogorytes Ashmead, 1899 (Hymenoptera: Crabronidae: Bembicinae) in India and description of a new species - Kumar, P. Girish; Dubey, Anil Kumar (Zootaxa, 2021)
The digger wasp genus Argogorytes Ashmead, 1899 is newly reported from India with two species: A. pulawskii Girish Kumar & Dubey sp. nov. from Andaman Islands and A. tonkinensis (Yasumatsu, 1943) from the States of Chhattisgarh and Kerala. Argogorytes tonkinensis (Yasumatsu, 1943) is redescribed. A key to Argogorytes species reported from the Indian subcontinent is provided.